Role of annealing temperature on optimizing the linear and nonlinear optical properties of As40Se50Ge10 films. Issue 45 (16th July 2020) - Sahoo, D.; Priyadarshini, P.; Aparimita, A.; Alagarasan, D.; Ganesan, R.; Varadharajaperumal, S.; Naik, R.
Abstract : The present work shows the effect of annealing conditions on the linear and nonlinear optical properties of two-year-old thermally evaporated 800 nm As40 Se50 Ge10 thin films. Abstract : The present work shows the effect of annealing conditions on the linear and nonlinear optical properties of two-year-old thermally evaporated 800 nm As40 Se50 Ge10 thin films. The aging effect in this film is clearly noticeable as compared with the old observation. The two-year-old films were annealed at different temperatures like 373, 413, 453 and 493 K for 1 h. The optical parameters were calculated from the optical transmittance and reflectance spectra measured at normal incidence of light by spectrometer in the 500–1000 nm range. The linear refractive index ( n ) and extinction coefficient ( k ) were decreased with annealing temperature. The observation reveals the increase in optical band gap with increase in annealing temperature while the width of the tail in the gap has an opposite behaviour. The oscillator energy, dispersion energy, dielectric constant, the loss factor, and optical conductivity were discussed in detail. The nonlinear refractive index and optical susceptibility were calculated by using Miller's formula which decreased with annealing temperature. The changes in both linear and nonlinear optical parameters with annealing temperature showed that annealing temperature can be considered as a useful factor for controlling the optical properties of As40 Se50 Ge10 chalcogenide films which could be the candidate for numerous photonic applications. The structural study was done by X-ray diffraction and Raman spectroscopy.